The Influence of Problem-Based Learning and Learning Motivation on Students’ Public Speaking Skill - Agus Darmuki; Nur Alfin Hidayati (IKIP PGRI Bojonegoro, 2026)
Public speaking skill is one of important skills in effective communication. However, there are many students get difficulties in it. This study aimed to investigate the influence of Problem-Based Learning (PBL) and learning motivation on students’ public speaking skill. This study was qualitative research in form of experimental method with factorial design of 2x2. Samples were taken using purposive sampling technique. The research instruments were performance test and questionnaire. This study showed that PBL had positive impact on students’ public speaking skill. The interaction between PBL and learning motivation influenced their ability in public speaking. This study concluded that PBL and learning motivation influenced students’ public speaking skill. Implication of this study was the use of PBL could be implemented in future studies to determine the effectiveness of PBL in different contexts.